The Effectiveness of a Group Guidance Service with a Humanistic Existential Approach based on Islamic Spiritual Values to Improve Students’ Discipline - Ikhsan Fauzi, Miftakhul; Sutoyo, Anwar; Purwanto, Edy (Jurnal Bimbingan Konseling, 2023)
Students’ discipline needs special attention in the aftermath of COVID-19 pandemic due to their online learning habit which somehow shifted the way they behaved during the pandemic. This study aimed to determine the effectiveness of a group guidance service with a humanistic existential approach based on Islamic spiritual values to improve students’ discipline. 20 students were involved as the samples and grouped into two, namely 10 for the experimental group and 10 for the control group. Here, the design was pretest and posttest, while the data were analyzed using a Wilcoxon test. Findings have proved that students’ discipline improved after receiving the group guidance service with a humanistic existential approach based on Islamic spiritual values. Thus, counselors are suggested to implement this intervention to improve students’ discipline